Sectoral and plurilateral approaches in services negotiations: Before and after TISA - Michitaka Nakatomi (European Centre for International Political Economy (ECIPE), 2015)
With the stagnation of services negotiations under the World Trade Organization (WTO), the Trade in Services Agreement (TISA) is currently the only framework that possesses the potential to advance direct global liberalisation and rulemaking. The plurilateral format, used as the next-best alternative, opens up new possibilities that would be impossible for any of its participants to achieve in isolation. This policy brief looks at the circumstances that led to the shortcomings of the General Agreement on Trade in Services (GATS) which in turn led to the inception of TISA. It also looks at the options that were available (in particular with regard to its legal form) before the negotiations took place as a free trade agreement outside the WTO. Moreover, it looks to how the TISA can eventually be multilateralised through sectoral agreements such as the GATS Annex approach, i.e. sector by sector, or issue by issue). If a universal agreement, based on reaching critical mass and extending the benefits according to the most-favoured nation (MFN) principle can be reached in individual sectors, there is potential to advance global services liberalisation from the TISA framework.
Keywords: 330; Dienstleistungshandel; Handelsabkommen; Handelsliberalisierung; Verhandlungen